Pemanfaatan Metafor Sufi Jemaah Tarekat Majelis Zikir Miftahul Bayan Kabupaten Lombok Tengah - Aswandikari, Aswandikari; Sukri, Sukri; Burhanuddin, Burhanuddin; Musaddat, Syaiful; Setiawan, Irma; Al-Faruq, Suhaib; Barmansyah, Muh. Sastrawan (Indonesian Journal of Education and Community Services, 2025)
This community service activity aims to enhance the spiritual understanding of the Jamaah Tarekat at Majelis Zikir Miftahul Bayan in Gapura Village, Pujut District, Central Lombok Regency. The activity was conducted on September 14, 2025, at Ponpes Miftahul Bayan, involving approximately 100 participants. Before implementation, coordination was established with the leaders of Tarekat Naksabandiyah to finalize the program’s model, schedule, and venue. The session commenced with opening remarks from the Chairperson of the Universitas Mataram service team and the leader of Tarekat Naksabandiyah. The core activity consisted of lectures preceded by zikir, selawatan, and zikir ngaji. The lectures focused on tasawuf (Sufism) teachings, which are characterized by expressions rich in symbols and metaphors, necessitating specialized interpretation for the jamaah. This is particularly significant given that the Jamaah Tarekat Naksabandiyah possesses a heterogeneous socio-cultural background, comprising farmers, traders, laborers, and the unemployed, alongside generally low levels of formal education. In this context, the lecture via zikir ngaji was delivered through pepaosan, the traditional recitation of lontar (palm-leaf) manuscripts containing tasawuf doctrines. A distinct feature of Sasak Sufi literature is its highly aesthetic and metaphoric linguistic style, which carries profound spiritual depth. Due to the complexity of such language and its inherent sufistic aspects, a competent teacher is required to provide comprehensive explanations to the congregation.